2010
DOI: 10.1007/s00520-010-0948-0
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in elderly cancer survivors—a population-based controlled study of associations with lifestyle, morbidity, and psychosocial factors. Results from the Health Survey of North-Trøndelag County (HUNT-2)

Abstract: Insomnia affects people physically, mentally and in their ability to perform ADL. Elderly cancer survivors with insomnia reported more physical and psychosocial problems compared to survivors without insomnia. Except for increased P-ADL problems, cancer survivors with insomnia reported similarly to cancer-free controls with insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…36 Older patients with cancer who have insomnia reported 15% higher rate of musculoskeletal diseases and gastro-intestinal symptoms. 20 In addition, 26% of older adults with cancer and insomnia also reported 'good health', which was significantly less compared to 46% in survivors without such symptoms. 20 Additionally, they reported more regular use of sleep medications, problems with performing activities of daily living including personal hygiene, dressing and eating, and higher levels of anxiety and depression.…”
Section: Effects Of Insomnia On Quality Of Life In Older Adults With mentioning
confidence: 98%
See 4 more Smart Citations
“…36 Older patients with cancer who have insomnia reported 15% higher rate of musculoskeletal diseases and gastro-intestinal symptoms. 20 In addition, 26% of older adults with cancer and insomnia also reported 'good health', which was significantly less compared to 46% in survivors without such symptoms. 20 Additionally, they reported more regular use of sleep medications, problems with performing activities of daily living including personal hygiene, dressing and eating, and higher levels of anxiety and depression.…”
Section: Effects Of Insomnia On Quality Of Life In Older Adults With mentioning
confidence: 98%
“…20 In older adults with cancer, a cross-sectional study revealed that those who experience pain, fatigue, and insomnia have lower quality of life and also had the greatest decrements in functioning. 34 In addition, they reported more physical and psychosocial problems.…”
Section: Effects Of Insomnia On Quality Of Life In Older Adults With mentioning
confidence: 99%
See 3 more Smart Citations